If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-6-5-13-(-25)=p
We simplify the equation to the form, which is simple to understand
2-6-5-13-(-25)=p
Remove unnecessary parentheses
2-6-5-13+25=p
We move all terms containing p to the left and all other terms to the right.
-1p=-2+6+5+13-25
We simplify left and right side of the equation.
-1p=-3
We divide both sides of the equation by -01 to get p.
p=3
| (2)(2)(2)= | | 8x-6x=-2 | | 28-(-8)-3=m | | x^2+x+0.5=0 | | 11d=11 | | X=-8+5x | | -12-25-32-(-9)=p | | -4-4=8-7x | | 15y=150 | | 14-.666666x=18 | | x+-24=10 | | 13.374x^2-258.431x+1724.415=0 | | -4x-5+x=4 | | -5(3q+9)=45 | | 15=.6n | | -4=4(6g-12)-2y | | 6-3x+2x=9x+26 | | .6x+22=28 | | -(4)(-2)= | | 3x-10=x+8 | | 3a-12b=x | | .5b=3 | | R=-6.25x^2+75x+1000 | | 0.55b=3 | | 3x-8=6x+8 | | -(10)= | | 14=5x-4x+8 | | .5x-29=-22 | | 8-3x=4+x | | 2p+22=-6p | | x+24=10 | | -(-9)= |